MEMS Actuators for Tuning Nanometer-scale Airgaps in Heterostructures and Optical Instrumentation for Glacier Ice Studies - Chan, Wing Shan (2016)
University of Minnesota Ph.D. dissertation. January 2016. Major: Electrical Engineering. Advisor: Joseph Talghader. 1 computer file (PDF); ix, 116 pages. MEMS Actuators for Tuning Nanometer-scale Airgaps in Heterostructures We developed a new actuator microstructure to control the spacing between closely spaced surfaces. Creating and controlling nanometer gaps is of interest in areas such as plasmonics and quantum electronics. For example, energy states in quantum well heterostructures can be tuned by adjusting the physical coupling distance between wells. Unfortunately, such an application calls for active control of a nano-scale air gap between surfaces which are orders of magnitude larger, which is difficult due to stiction forces. A vertical electrostatic wedge actuator was designed to control the air gap between two closely spaced quantum wells in a collapsed cantilever structure. A six-mask fab- rication process was developed and carried out on an InGaAs/InP quantum well het- erostructure on an InP substrate. Upon actuation, the gap spacing between the surfaces was tuned over a maximum range of 55 nm from contact with an applied voltage of 60 V. Challenges in designing and fabricating the device are discussed. Optical Instrumentation for Glacier Ice Studies We explored new optical instrumentation for glacier ice studies. Glacier ice, such as that of the Greenland and Antarctic ice sheets, is formed by the accumulation of snowfall over hundreds of thousands of years. Not all snowfalls are the same. Their isotopic compositions vary according to the planet’s climate at the time, and may contain part of the past atmosphere. The physical properties and chemical content of the ice are therefore proxies of Earth’s climate history. In this work, new optical methods and instrumentation based on light scattering and polarization were developed to more efficiently study glacier ice. Field deployments in Antarctica of said instrumentation and results acquired are presented.